Lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic as well as preparation method and application thereof
By introducing lead niobium indium niobium in solid solution and adding Bi2O3, stable lead niobium indium niobium indium niobium indium scandium-lead titanate ternary piezoelectric ceramics are formed, which solves the problems of depolarization and increased conductance of traditional piezoelectric ceramics at high temperatures, and the combination of high Curie temperature and excellent piezoelectric properties is achieved.
Patent Information
- Application Number
- CN202411807612.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional lead zirconium titanate-based piezoelectric ceramic materials have depolarization and increased conductance in high-temperature environments, which is difficult to meet the stable work needs of aerospace, petroleum survey, defense and military industries for higher temperatures.
By introducing lead niobium indium niobium indium scummate-lead titanate binary solid solution, piezoelectric ceramics with a ternary system of lead niobium indium indium scandium-lead scandium-lead titanate, and an appropriate amount of Bi2O3 was added during the sintering process to compensate for the volatility of Pb ions, improving the structural stability and piezoelectric properties of ceramic materials.
It achieves high Curie temperature and excellent piezoelectric properties, enhances the structural stability of ceramic materials, reduces the production cost, and is suitable for large-scale production.
Smart Images

Figure CN119874332A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional ceramics, and in particular relates to a lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic and a preparation method and application thereof. Background Art
[0002] Piezoelectric ceramics are functional ceramic materials that can convert mechanical energy and electrical energy into each other. Their unique piezoelectric effect makes them have important application value in the fields of piezoelectric igniters, sensors, drivers and transducers. At present, the most widely used piezoelectric materials in commercial applications are lead zirconate titanate-based piezoelectric ceramics, whose Curie temperature is generally between 250-380℃. Due to the potential depolarization and increased conductivity in a warming environment, their safe use temperature is generally limited to around 1 / 2 Curie temperature. With the rapid development of science and technology, piezoelectric components that can work stably at higher temperatures are urgently needed in important fields such as aerospace, petroleum exploration and national defense. Traditional lead zirconate titanate-based piezoelectric ceramic materials can no longer meet the needs of new industries for higher application temperatures. Therefore, the development of piezoelectric ceramic materials with high Curie temperatures, that is, piezoelectric ceramic materials that can work stably for a long time in a high temperature environment without depolarization, has become one of the hot spots that countries are committed to research and development.
[0003] Bismuth scandate-lead titanate BiScO3-PbTiO3 (BS-PT) solid solution is a high-temperature piezoelectric ceramic material with excellent performance and a high Curie temperature T C ≈450℃, which has potential application value in the field of high-temperature piezoelectricity. However, the scandium raw materials used to synthesize bismuth scandate-lead titanate ceramics are expensive, which greatly limits their large-scale commercial applications. In addition, the tolerance factor of bismuth scandate-lead titanate solid solution near the quasi-isotropic phase boundary is 0.908, which is close to but does not completely meet the stability conditions of the perovskite structure, which makes the perovskite structure very unstable after sintering. Therefore, bismuth scandate-lead titanate piezoelectric ceramics are not easy to synthesize using traditional preparation methods, and their process requirements are strict and the repeatability is poor. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic and a preparation method and application thereof, the piezoelectric ceramic has a stable structure, high Curie temperature and piezoelectric properties, and has broad application prospects in the field of high-temperature piezoelectric devices.
[0005] In order to solve the above technical problems, the first aspect of the present invention provides a lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic, the chemical formula of which is xPb(In 1 / 2 Nb 1 / 2)O3-(1-xy)BiScO3-yPbTiO3+zBi2O3, wherein: 0.02≤x≤0.06, 0.5≤y≤0.7, 0.5%≤z≤1.5%, x and y represent molar ratios, and z represents mass ratio.
[0006] Specifically, the present invention introduces lead indium niobate as the third component into the bismuth scandate-lead titanate binary solid solution to form a piezoelectric ceramic of the lead indium niobate-bismuth scandate-lead titanate ternary system. The tolerance factor of the lead indium niobate-lead titanate solid solution near the quasi-morphic phase boundary is 0.965, which is much higher than the tolerance factor of the bismuth scandate-lead titanate solid solution near the quasi-morphic phase boundary. Therefore, by introducing lead indium niobate into the bismuth scandate-lead titanate solid solution, its lattice structure can be adjusted, the tolerance factor can be improved, thereby enhancing the stability of the structure, improving the thermodynamic instability of the bismuth scandate-lead titanate system, and then obtaining excellent electrical properties. At the same time, the quasi-isotropic phase boundary component is extended from the point of the bismuth scandate-lead titanate binary solid solution to the line of the lead indium niobate-bismuth scandate-lead titanate ternary solid solution, which has greater component adjustability and electrical performance adjustability; and the introduction of lead indium niobate can also reduce the content of scandium ions in the bismuth scandate-lead titanate system, reducing the preparation cost. In addition, since Pb ions and Bi ions are easily volatilized to form ion vacancies during high-temperature sintering, the present invention adds an appropriate amount of Bi2O3 to compensate for the volatilization of ions during the sintering process, and the excess Bi ions can also replace the Pb ions volatilized during the sintering process, playing a doping role, thereby further improving the piezoelectric properties of the ceramic material.
[0007] In some embodiments of the present invention, the value ranges of x, y and z are: 0.025≤x≤0.05, 0.58≤y≤0.62, 0.5%≤z≤1%, respectively.
[0008] The second aspect of the present invention provides a method for preparing the above-mentioned lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic, comprising the following steps:
[0009] (1) Sc2O3, Bi2O3, PbO, In2O3, Nb2O5, TiO2 are mixed according to the chemical formula xPb(In 1 / 2 Nb 1 / 2 )O3-(1-xy)BiScO3-yPbTiO3 in a stoichiometric ratio, and after ball milling, drying and pre-calcining, a pre-calcined powder is obtained;
[0010] (2) adding an organic binder and Bi2O3 powder to the pre-sintered powder, and sequentially performing ball milling, drying, sieving, and pressing to obtain a ceramic green body;
[0011] (3) debinding the ceramic green body and then sintering it to obtain a dense ceramic;
[0012] (4) The dense ceramic surface is polished, silvered, and polarized to obtain the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic.
[0013] Specifically, when preparing the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic of the present invention, the raw materials are first mixed in a stoichiometric ratio, and then the raw materials are reacted through solid phase sintering to generate a pre-fired powder with a perovskite structure; then excess bismuth ions are added to promote sintering, thereby obtaining a stable and dense ceramic block, thereby improving the stability and high piezoelectric properties of the ceramic material.
[0014] In some embodiments of the present invention, in step (1) and step (2), the process parameters of the ball milling are: using anhydrous ethanol as the ball milling medium and ball milling at a rotation speed of 200-300 r / min for 6-12 hours.
[0015] In some embodiments of the present invention, in step (1) and step (2), the mass ratio of the ball-milled material to the ball-milled medium is 1:(0.75-1.5).
[0016] In some embodiments of the present invention, in step (1), the pre-calcination temperature is 800-850°C.
[0017] In some embodiments of the present invention, in step (1), the pre-firing holding time is 1-2 hours.
[0018] In some embodiments of the present invention, in step (2), the amount of Bi2O3 powder added is 0.5-1.5wt% of the pre-calcined powder.
[0019] In some embodiments of the present invention, in step (2), the organic binder is selected from Rhoplex solution.
[0020] In some embodiments of the present invention, in step (2), the amount of the organic binder added is 2-4 wt % of the pre-calcined powder.
[0021] In some embodiments of the present invention, in step (3), the debinding temperature is 550-650°C.
[0022] In some embodiments of the present invention, in step (3), the debinding holding time is 1-2 hours.
[0023] In some embodiments of the present invention, in step (3), the sintering temperature is 1150-1190°C.
[0024] In some embodiments of the present invention, in step (3), the sintering holding time is 2-4 hours.
[0025] The above-mentioned holding time refers to the holding time at the highest pre-firing temperature, debinding temperature or sintering temperature.
[0026] In some embodiments of the present invention, in step (3), the polarization process parameters are: polarization for 10-20 minutes at a temperature of 100-120° C. and an electric field of 30-40 kV / cm.
[0027] The third aspect of the present invention provides an electronic component, comprising the above-mentioned lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic.
[0028] In some embodiments of the present invention, the electronic component is a high-temperature piezoelectric device.
[0029] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0030] (1) The present invention introduces lead indium niobate as the third component into the bismuth scandate-lead titanate binary solid solution to form a piezoelectric ceramic of the lead indium niobate-bismuth scandate-lead titanate ternary system. The introduction of lead indium niobate is conducive to adjusting the lattice structure of the bismuth scandate-lead titanate solid solution, improving the tolerance factor, thereby enhancing the stability of the structure, improving the thermodynamic instability of the bismuth scandate-lead titanate system, and thus obtaining excellent electrical properties. At the same time, the quasi-morphous phase boundary component expands from the point of the bismuth scandate-lead titanate binary solid solution to the line of the lead indium niobate-bismuth scandate-lead titanate ternary solid solution, which has greater component adjustability and electrical performance adjustability.
[0031] (2) The present invention reduces the content of scandium ions in the bismuth scandate-lead titanate system by introducing lead indium niobate into the bismuth scandate-lead titanate binary solid solution, thereby reducing the preparation cost. At the same time, the present invention adds an excess of Bi2O3 to compensate for the Pb ions volatilized during the sintering process, thereby playing a doping role, thereby further improving the piezoelectric properties of the ceramic material.
[0032] (3) The present invention adopts the traditional solid phase synthesis method to prepare lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramics. The preparation method is simple and suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The XRD diffraction pattern of the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic prepared in Example 1 of the present invention;
[0034] Figure 2 This is a SEM scanning electron microscope image of the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic prepared in Example 1 of the present invention;
[0035] Figure 3 This is the dielectric temperature spectrum of the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0037] Example 1
[0038] A lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic, the chemical formula of which is: 0.05Pb(In 1 / 2 Nb 1 / 2 )O3-0.37BiScO3-0.58PbTiO3+0.5wt%Bi2O3. The preparation method of the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic comprises the following steps:
[0039] (1) According to the chemical formula 0.05Pb(In 1 / 2 Nb 1 / 2 )O3-0.37BiScO3-0.58PbTiO3 stoichiometric ratio: weigh Sc2O3, Bi2O3, PbO, In2O3, Nb2O5, TiO2, then put each raw material into a ball mill for 6 hours (the medium of ball milling is anhydrous ethanol, and the mass ratio of material to anhydrous ethanol is 1:0.75), after drying, put it into an alumina crucible, and then put it into a muffle furnace, heat it to 850°C at a rate of 2°C / min and keep it warm for 1 hour to obtain a pre-sintered powder;
[0040] (2) adding Rhoplex binder (the amount added is 4 wt% of the mass of the pre-fired powder) and Bi2O3 powder (the amount added is 0.5 wt% of the mass of the pre-fired powder) to the pre-fired powder obtained in step (1), then placing it in a ball mill for ball milling for 12 hours (the medium for ball milling is anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol is 1:1), then placing it in a 100° C. oven for drying, and finally placing it in an agate mortar for grinding, passing through an 80-mesh sieve, and using a mold to press it into a round ceramic green body;
[0041] (3) placing the ceramic green body obtained in step (2) into a muffle furnace, heating the sample to 550° C. at a rate of 2° C. / min and keeping the temperature for 2 hours, and then placing the sample after debinding into a sealed crucible; heating the sample to 1180° C. at a rate of 2° C. / min and keeping the temperature for 2 hours to sinter, and naturally cooling the sample to room temperature in the furnace to obtain a dense ceramic;
[0042] (4) The dense ceramic obtained in step (3) is ground and polished, and then silver electrodes are coated on both sides of the polished dense ceramic. The ceramic is placed in silicone oil at 100° C., and an electric field of 40 kV / cm is applied and maintained for 10 minutes to obtain the lead indium oxide-bismuth scandate-lead titanate piezoelectric ceramic of this embodiment.
[0043] Performance testing and characterization:
[0044] (1) The lead indium oxide-bismuth scandate-lead titanate piezoelectric ceramic prepared in Example 1 was subjected to an X-ray diffraction (XRD) test. The results are as follows: Figure 1 As shown, Figure 1 The horizontal axis "2θ" represents the diffraction angle, and the vertical axis "Intensity" represents the diffraction intensity. Figure 1 It can be seen that the piezoelectric ceramic has a single perovskite structure without any impurity phase, indicating that lead indium niobate has formed a stable solid solution structure with bismuth scandate-lead titanate.
[0045] (2) The lead indium oxide-bismuth scandate-lead titanate piezoelectric ceramics sintered in Example 1 were tested by scanning electron microscopy (SEM). The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the piezoelectric ceramic has uniform grains and high density, and no obvious pores are observed.
[0046] (3) The lead indium oxide-bismuth scandate-lead titanate piezoelectric ceramics prepared in Example 1 were tested for dielectric temperature performance. The results are as follows: Figure 3 As shown, Figure 3 The horizontal axis "Temperature" represents temperature, and the vertical axis "Dielectric constant" represents dielectric constant. Figure 3 It can be seen that the Curie temperature of the piezoelectric ceramic is around 396°C, and a high Curie temperature is conducive to stable operation in a high temperature environment.
[0047] (4) The lead indium oxide-bismuth scandate-lead titanate piezoelectric ceramic prepared in Example 1 was placed in a 33 The piezoelectric constant was measured to be 340pC / N in a quasi-static analyzer.
[0048] Example 2
[0049] A lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic, the chemical formula of which is: 0.05Pb(In 1 / 2 Nb 1 / 2 )O3-0.34BiScO3-0.61PbTiO3+0.5wt%Bi2O3. The preparation method of the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic comprises the following steps:
[0050] (1) According to the chemical formula 0.05Pb(In 1 / 2 Nb 1 / 2 )O3-0.34BiScO3-0.61PbTiO3 stoichiometric ratio: weigh Sc2O3, Bi2O3, PbO, In2O3, Nb2O5, and TiO2, then put each raw material into a ball mill for 12 hours (the ball milling medium is anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol is 1:1), after drying, put it into an alumina crucible, and then put it into a muffle furnace, heat it to 800°C at a rate of 2°C / min and keep it warm for 2 hours to obtain a pre-sintered powder;
[0051] (2) adding Rhoplex binder (the amount added is 4 wt% of the mass of the pre-fired powder) and Bi2O3 powder (the amount added is 0.5 wt% of the mass of the pre-fired powder) to the pre-fired powder obtained in step (1), then placing it in a ball mill for ball milling for 12 hours (the medium for ball milling is anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol is 1:1), then placing it in a 100° C. oven for drying, and finally placing it in an agate mortar for grinding, passing through an 80-mesh sieve, and using a mold to press it into a round ceramic green body;
[0052] (3) placing the ceramic green body obtained in step (2) into a muffle furnace, heating the temperature to 550° C. at a rate of 2° C. / min and keeping the temperature for 2 hours, then placing the sample after debinding into a sealed crucible; then heating the temperature to 1190° C. at a rate of 2° C. / min and keeping the temperature for 2 hours to sinter, and naturally cooling to room temperature with the furnace to obtain a dense ceramic;
[0053] (4) The dense ceramic obtained in step (3) is ground and polished, and then silver electrodes are coated on both sides of the polished dense ceramic. The ceramic is placed in silicone oil at 120° C., and an electric field of 30 kV / cm is applied and maintained for 20 minutes to obtain the lead indium oxide-bismuth scandate-lead titanate piezoelectric ceramic of this embodiment.
[0054] The lead indium oxide-bismuth scandate-lead titanate piezoelectric ceramics prepared in Example 2 were placed in a 33 The piezoelectric constant was measured to be 490pC / N in a quasi-static analyzer.
[0055] Example 3
[0056] A lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic, the chemical formula of which is: 0.025Pb(In 1 / 2 Nb 1 / 2 )O3-0.355BiScO3-0.62PbTiO3+1wt%Bi2O3. The preparation method of the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic comprises the following steps:
[0057] (1) According to the chemical formula 0.025Pb(In1 / 2 Nb 1 / 2 )O3-0.355BiScO3-0.62PbTiO3 stoichiometric ratio: weigh Sc2O3, Bi2O3, PbO, In2O3, Nb2O5, TiO2, then put each raw material into a ball mill for 12 hours (the medium of ball milling is anhydrous ethanol, and the mass ratio of material to anhydrous ethanol is 1:1.5), after drying, put it into an alumina crucible, and then put it into a muffle furnace, heat it to 850°C at a rate of 2°C / min and keep it warm for 1 hour to obtain a pre-sintered powder;
[0058] (2) adding Rhoplex binder (the amount added is 4 wt% of the mass of the pre-fired powder) and Bi2O3 powder (the amount added is 1 wt% of the mass of the pre-fired powder) to the pre-fired powder obtained in step (1), then placing it in a ball mill for ball milling for 6 hours (the medium for ball milling is anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol is 1:1), then placing it in a 100° C. oven for drying, and finally placing it in an agate mortar for grinding, passing through an 80-mesh sieve, and using a mold to press it into a round ceramic green body;
[0059] (3) placing the ceramic green body obtained in step (2) into a muffle furnace, heating the temperature to 600° C. at a rate of 2° C. / min and keeping the temperature for 1 hour, then placing the sample after debinding into a sealed crucible; then heating the temperature to 1150° C. at a rate of 2° C. / min and keeping the temperature for 4 hours to sinter, and naturally cooling to room temperature with the furnace to obtain a dense ceramic;
[0060] (4) The dense ceramic obtained in step (3) is ground and polished, and then silver electrodes are coated on both sides of the polished dense ceramic. The ceramic is placed in silicone oil at 120° C., and an electric field of 30 kV / cm is applied and maintained for 20 minutes to obtain the lead indium oxide-bismuth scandate-lead titanate piezoelectric ceramic of this embodiment.
[0061] The lead indium oxide-bismuth scandate-lead titanate piezoelectric ceramics prepared in Example 3 were placed in a 33 The piezoelectric constant was measured to be 380pC / N in a quasi-static analyzer.
[0062] Comparative Example 1
[0063] A lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic, the chemical formula of which is: 0.025Pb(In 1 / 2 Nb 1 / 2 )O3-0.355BiScO3-0.62PbTiO3. The preparation method of the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic comprises the following steps:
[0064] (1) According to the chemical formula 0.025Pb(In 1 / 2 Nb 1 / 2)O3-0.355BiScO3-0.62PbTiO3 stoichiometric ratio: weigh Sc2O3, Bi2O3, PbO, In2O3, Nb2O5, TiO2, then put each raw material into a ball mill for 12 hours (the medium of ball milling is anhydrous ethanol, and the mass ratio of material to anhydrous ethanol is 1:1.5), after drying, put it into an alumina crucible, and then put it into a muffle furnace, heat it to 850°C at a rate of 2°C / min and keep it warm for 1 hour to obtain a pre-sintered powder;
[0065] (2) adding Rhoplex binder (the amount added is 4 wt% of the mass of the pre-fired powder) to the pre-fired powder obtained in step (1), then placing it in a ball mill for 6 hours (the medium for ball milling is anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol is 1:1), then placing it in a 100° C. oven for drying, and finally placing it in an agate mortar for grinding, passing through an 80-mesh sieve, and pressing it into a round ceramic green body using a mold;
[0066] (3) placing the ceramic green body obtained in step (2) into a muffle furnace, heating the temperature to 600° C. at a rate of 2° C. / min and keeping the temperature for 1 hour, then placing the sample after debinding into a sealed crucible; then heating the temperature to 1150° C. at a rate of 2° C. / min and keeping the temperature for 4 hours to sinter, and naturally cooling to room temperature with the furnace to obtain a dense ceramic;
[0067] (4) The dense ceramic obtained in step (3) is ground and polished, and then silver electrodes are coated on both sides of the polished dense ceramic, and then placed in silicone oil at 120° C., an electric field of 30 kV / cm is applied and maintained for 20 minutes to obtain the lead indium oxide-bismuth scandate-lead titanate piezoelectric ceramic of this comparative example.
[0068] The lead indium oxide-bismuth scandate-lead titanate piezoelectric ceramic prepared in Comparative Example 1 was placed in a 33 The piezoelectric constant was measured to be 350pC / N in a quasi-static analyzer.
[0069] Comparative Example 2
[0070] A bismuth scandate-lead titanate piezoelectric ceramic, whose chemical formula is: 0.38BiScO3-0.62PbTiO3. The preparation method of the bismuth scandate-lead titanate piezoelectric ceramic comprises the following steps:
[0071] (1) Sc2O3, Bi2O3, PbO, and TiO2 were weighed according to the stoichiometric ratio of the chemical formula 0.38BiScO3-0.62PbTiO3, and then the raw materials were placed in a ball mill for 12 hours (the medium for ball milling was anhydrous ethanol, and the mass ratio of the material to the anhydrous ethanol was 1:1.5). After drying, the raw materials were placed in an alumina crucible, and then placed in a muffle furnace, and the temperature was increased to 850°C at a rate of 2°C / min and kept at this temperature for 1 hour to obtain a pre-calcined powder;
[0072] (2) adding Rhoplex binder (the amount added is 4 wt% of the mass of the pre-fired powder) to the pre-fired powder obtained in step (1), then placing it in a ball mill for 6 hours (the medium for ball milling is anhydrous ethanol, and the mass ratio of the material to anhydrous ethanol is 1:1), then placing it in a 100° C. oven for drying, and finally placing it in an agate mortar for grinding, passing through an 80-mesh sieve, and pressing it into a round ceramic green body using a mold;
[0073] (3) placing the ceramic green body obtained in step (2) into a muffle furnace, heating the temperature to 600° C. at a rate of 2° C. / min and keeping the temperature for 1 hour, then placing the sample after debinding into a sealed crucible; then heating the temperature to 1150° C. at a rate of 2° C. / min and keeping the temperature for 4 hours to sinter, and naturally cooling to room temperature with the furnace to obtain a dense ceramic;
[0074] (4) The dense ceramic obtained in step (3) is ground and polished, and then silver electrodes are coated on both sides of the polished dense ceramic, and then placed in silicone oil at 120° C., an electric field of 30 kV / cm is applied and maintained for 20 minutes to obtain the bismuth scandate-lead titanate piezoelectric ceramic of this comparative example.
[0075] The bismuth scandate-lead titanate piezoelectric ceramics prepared in Comparative Example 2 were placed in a 33 The piezoelectric constant was measured to be 180pC / N in a quasi-static analyzer.
[0076] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic, characterized in that: Its chemical formula is xPb(In 1 / 2 Nb 1 / 2 )O3-(1-xy)BiScO3-yPbTiO3+zBi2O3, wherein: 0.02≤x≤0.06, 0.5≤y≤0.7, 0.5%≤z≤1.5%, x and y represent molar ratios, and z represents mass ratio.
2. The lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic according to claim 1, characterized in that: The value ranges of x, y and z are respectively: 0.025≤x≤0.05, 0.58≤y≤0.62, 0.5%≤z≤1%.
3. A method for preparing the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic according to claim 1 or 2, characterized in that: The following steps are involved: (1) Sc2O3, Bi2O3, PbO, In2O3, Nb2O5, TiO2 are mixed according to the chemical formula xPb(In 1 / 2 Nb 1 / 2 )O3-(1-xy)BiScO3-yPbTiO3 in a stoichiometric ratio, and after ball milling, drying and pre-calcining, a pre-calcined powder is obtained; (2) adding an organic binder and Bi2O3 powder to the pre-sintered powder, and sequentially performing ball milling, drying, sieving, and pressing to obtain a ceramic green body; (3) debinding the ceramic green body and then sintering it to obtain a dense ceramic; (4) The dense ceramic surface is polished, silvered, and polarized to obtain the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic.
4. The method for preparing the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic according to claim 3, characterized in that: In step (1) and step (2), the process parameters of the ball milling are: using anhydrous ethanol as the ball milling medium and ball milling at a rotation speed of 200-300 r / min for 6-12 hours.
5. The method for preparing the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic according to claim 3, characterized in that: In step (1), the pre-firing temperature is 800-850° C.; and / or the pre-firing holding time is 1-2 hours.
6. The method for preparing the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic according to claim 3, characterized in that: In step (2), the amount of Bi2O3 powder added is 0.5-1.5wt% of the pre-calcined powder.
7. The method for preparing the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic according to claim 3, characterized in that: In step (3), the temperature of the debinding is 550-650° C.; and / or the insulation time of the debinding is 1-2 hours.
8. The method for preparing the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic according to claim 3, characterized in that: In step (3), the sintering temperature is 1150-1190° C.; and / or the sintering holding time is 2-4 hours.
9. The method for preparing the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic according to claim 3, characterized in that: In step (3), the polarization process parameters are: polarization for 10-20 minutes at a temperature of 100-120° C. and an electric field of 30-40 kV / cm.
10. An electronic component, characterized in that: It includes the lead indium niobate-bismuth scandate-lead titanate piezoelectric ceramic as described in claim 1 or 2.